2018
DOI: 10.1093/jpids/piy113
|View full text |Cite|
|
Sign up to set email alerts
|

Implementation of a Pragmatic Biomarker-Driven Algorithm to Guide Antibiotic Use in the Pediatric Intensive Care Unit: the Optimizing Antibiotic Strategies in Sepsis (OASIS) II Study

Abstract: Background Biomarkers can facilitate safe antibiotic discontinuation in critically ill patients without bacterial infection. Methods We tested the ability of a biomarker-based algorithm to reduce excess antibiotic administration in patients with systemic inflammatory response syndrome (SIRS) without bacterial infections (uninfected) in our pediatric intensive care unit (PICU). The algorithm suggested that PICU clinicians stop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 25 publications
0
27
0
1
Order By: Relevance
“…A primary goal of the study was to assess whether CRP, which had previously been found to be predictive of bacterial infection (Downes et al, 2017), could be used to determine when antibiotic therapy could be safely ended. Additional details of the study design and results of the primary analysis may be found in Downes et al (2018).…”
Section: Numerical Studiesmentioning
confidence: 99%
“…A primary goal of the study was to assess whether CRP, which had previously been found to be predictive of bacterial infection (Downes et al, 2017), could be used to determine when antibiotic therapy could be safely ended. Additional details of the study design and results of the primary analysis may be found in Downes et al (2018).…”
Section: Numerical Studiesmentioning
confidence: 99%
“…These findings were similar to the OASIS II Study in which investigators found the biggest impact among a subgroup of patients with low biomarker levels at onset of systemic inflammatory response syndrome (SIRS). 17 In many of our subgroup analyses, including patients with pneumonia and possible sepsis, we found shorter DOT in the PCT vs. usual care arm, but these were not statistically significant differences, likely due to small sample sizes.…”
Section: Discussionmentioning
confidence: 60%
“…To our knowledge, there are no published RCTs comparing PCT-based discontinuation to standard-of-care treatment in older pediatric patients. However, observational studies are available (62). One study evaluated the impact of an algorithm on antibiotic use in critically ill children with SIRS (62).…”
Section: Antimicrobial Stewardshipmentioning
confidence: 99%
“…However, observational studies are available (62). One study evaluated the impact of an algorithm on antibiotic use in critically ill children with SIRS (62). The algorithm indicated cessation of antibiotics at 24 to 48 h if PCT levels determined at SIRS onset were Ͻ1 ng/ml and CRP levels were Ͻ4 mg/dl, microbiological cultures were negative, and there were no focal signs of infection present on evaluation.…”
Section: Antimicrobial Stewardshipmentioning
confidence: 99%
See 1 more Smart Citation